CHARACTER ESTABLISHMENT THROUGH ISLAMIC RELIGIOUS EDUCATION - Imam Tabroni; Ahmad Paisal; Rafani Aura Suci; Zakiyah (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This composing is introducing about the job of Islamic Religious Education example toward understudies. Islamic Religious Education is probably the most significant pillar of character instruction. Character instruction will construct well, assuming that it is begun from developing strict feeling of understudies, along these lines, Islamic Education illustration become one of supporting example of character schooling. Through Islamic Education instructing and learning, the understudies is shown conviction of God as the fundamental of their religion, showed al quran and hadith as their lifestyle, educated fiqh as law signs in doing Islam instructing, educated Islam history as a decent life model, and instructed ethics as the method of human Character.